2018
DOI: 10.1167/iovs.18-24007
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Morphologic Alterations in Mechanical, Polymodal, and Cold Sensory Nerve Fibers of the Cornea Following Photorefractive Keratectomy

Abstract: PURPOSE. To define the characteristics and time course of the morphologic and functional changes experienced by corneal sensory nerves after photorefractive keratectomy (PRK).METHODS. Unilateral corneal excimer laser photoablation was performed in 54 anesthetized 3-to 6-month-old mice; 11 naïve animals served as control. Mice were killed 0, 3, 7, 15, and 30 days after PRK. Excised eyes were placed in a recording chamber superfused at 348C. Electrical nerve impulse activity of single sensory terminals was recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 54 publications
3
35
1
Order By: Relevance
“…The pattern of regenerative growth shown by identified TRPM8(ϩ) thermoreceptor fibers after surgical axotomy is essentially the same as that recently reported for corneal fibers of all sensory modalities after excimer laser ablation of the central cornea (Bech et al, 2018). This suggests that TG neurons of different sensory modalities share the general cellular mechanisms governing the anatomical distribution plan of regenerating axons after injury.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The pattern of regenerative growth shown by identified TRPM8(ϩ) thermoreceptor fibers after surgical axotomy is essentially the same as that recently reported for corneal fibers of all sensory modalities after excimer laser ablation of the central cornea (Bech et al, 2018). This suggests that TG neurons of different sensory modalities share the general cellular mechanisms governing the anatomical distribution plan of regenerating axons after injury.…”
Section: Discussionsupporting
confidence: 83%
“…Regenerating cold thermoreceptors displayed an enhanced ongoing activity 3 weeks after mechanical stromal parent axon's axotomy, a procedure that preserved only a few intact stromal branches in the hinge. This result contrasts with the low background activity in the majority of corneal cold terminals after a superficial excimer laser corneal lesion, where only the epithelium nerve branches and a fraction of the superficial stromal nerve trunks were destroyed (Bech et al, 2018). In this case, many parent axons maintained part of their complex branching tree intact, and only 20% of the recorded, regenerating cold nerve terminals exhibited abnormal background firing and lower threshold (i.e., higher sensitivity) to cooling stimuli, possibly corresponding to more severely injured axons.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Surgical injury was performed using an Allegretto WaveLight excimer laser (PR-020407, Wavelight GmbH, Alcon, Erlangen, Germany) as previously described. [26][27][28][29][30] Right eyes were subjected to PRK surgery with a 2.0-mm ablation zone on the central cornea and a depth of 45 μm. The procedure included the simultaneous ablation of the epithelium (using a defined epithelial thickness profile of 25 μm centrally) and 20 μm of the anterior stroma (about 20% of the total stromal thickness) in a single step.…”
Section: Prk Mouse Modelmentioning
confidence: 99%
“…As a result, in recent times, there has been a proliferation of research, especially using mouse animal models of corneal injury and nerve regeneration (e.g. Bech et al, 2018;Harris et al, 2018;Ozaki et al, 2018;Stepp et al, 2018;Zhang et al, 2018). Several of these studies have shown an interplay between immune cells and corneal nerves (e.g.…”
Section: Introductionmentioning
confidence: 99%